Economic Sustainability Analysis of Gaushalas in select Districts of Telangana State - Sivaram, Muniandy; Rohith, Siguram; Pradeep, Raju; Subash, Somasekaran (Indian Journal of Dairy Science, 2021)
In India, with the increasing cattle population the number of stray cattle has also been increasing. While indigenous cattle constitute a major portion of the total cattle population their proportion has been showing a declining trend. Gaushalas can serve as an alternative for housing the increasing stray cattle and also for preserving the indigenous germplasm. However, Â Gaushalas are functioning with insufficient funds mostly from donations and government grant. In this this study, an attempt was made to undertake economic sustainability analysis of Gaushalas by covering 14 Gaushalas in select districts of Telangana state. The data were collected from Gaushalas for the period 2014 to 2019 using a semi structured interview schedule. It was found that the major source of income to Gaushalas was from donations (82.5 per cent) followed by income from sale of milk and milk products (12.9 per cent). The expenses of the Gaushalas mainly included feed and fodder cost (82.5 per cent) followed by veterinary and miscellaneous expenditure (6.7 per cent). The overall net income for all the Gaushalas was negative. The returns over variable cost were positive for almost all the Gaushalas indicating that the Gaushalas were able to meet their immediate expenses in the short run. The overall operating ratio of 0.98 indicates that most of the Gaushalas were just able to cover their operating expenses. The overall fixed ratio was at 1.04 indicating that the Gaushalas were not able to cover variable and fixed expenses completely. Economic Sustainability Index (ESI) was computed which ranges from 0 to 1 using 5 indicators viz., net income per animal, returns over variable cost, self-sufficiency, dependency and percentage of productive animals. The values of ESI of the Gaushalas ranged from 0.302 to 0.471. Of 14 sample Gaushalas 2 Gaushalas fell under low economic sustainability and rest 12 Gaushalas were under medium economic sustainability category. A positive relationship was found between income diversification and sustainability of the Gaushalas. So, there is a need to diversify income sources such as income from sale of milk, milk products and other by-products.